Laser cutting of square blanks in stainless steel-304 sheets: HAZ and thermal stress analysis - A.M. Sifullah,; Ahmed, Khaled I.; Y. Nukman,; M.A. Hassan,; A. Hossain, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Laser cutting is a non-traditional cutting process and cutting of square blank in stainless steel-304 sheets cause heat affected zone (HAZ) and thermal stress. Formation of HAZ is undesirable and excessive stress cause surface defects. Thus, it is necessary to analyze them intensively. The process of laser cutting is a complex thermo-mechanical process. Hence, in this study a thermo-mechanical finite element model has been introduced by ANSYS to predict the temporal variation together with thermal stress and width of heat affected zone (HAZ). CO2 laser is used to cut 10 × 10 mm square blank in a 3 mm thick stainless steel-304 sheet. Optical microscope and SEM are used to analyse the parametric effect on surface quality at the cutting edge. The results showed that maximum temperature at the cutting edge is about to melting temperature and independent to laser power and cutting speed. Importantly, cutting speed has significant effect on rate of temperature variation. Moreover, the width of HAZ increases with the increase of laser power and decrease of cutting speed. However results of ANOVA suggested that laser power is the most significant parameter having 64.21% of contribution to width of HAZ. Furthermore, maximum stress is observed at the corner; which is supported by SEM analysis.